First Report of Phytopythium vexans (de Barry) Abad, de Cock, Bala, Robideau, Lodhi & Lévesque Causing Potato Tuber Rot in Indonesia - Islaminati Anna Santika; Ani Widiastuti; Arif Wibowo (Universitas Gadjah Mada, 2021)
Phytopythium vexans (de Barry) Abad, de Cock, Bala, Robideau, Lodhi & Lévesque was successfully isolated from soil of potato fields in Ngablak, Magelang. This research aimed to obtain the knowledge of P. vexans potency as a pathogen in potatoes, and also morphologically and molecularly identify P. vexans compared to the Oomycetes, Phytophthora and Pythium. Morphological identification was conducted by observing macroscopic colony pattern that grew on PDA medium for five days and microscopic observation on its hyphae, sporangia, papillate, and chlamydospore. Molecular identification was conducted using multigene analysis, ITS and LSU. The in vitro pathogenicity test was obtained by inoculating P. vexans inoculum to healthy potato leaves and tubers. Results of morphological observation showed that P. vexans had a stellate pattern, aseptate hyphae, ovoid shaped sporangium and completed with semipapillate. Chlamydospores were also found and often used for survival. This research revealed that the morphology characters of P. vexans were combination between the characteristics of Pythium and Phytophthora. Whereas, based on the molecular analysis using ITS and LSU, Phytopythium spp. was more closely related to Phytophthora spp. rather than Pythium spp. The pathogenicity test of P. vexans showed that it could infect the flesh of potato tubers by showing a brown lesions symptom